Advancements in Mechanical Power Transmission and Its Elements (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint brings together cutting-edge studies on mechanical power transmission systems and components that play a pivotal role across various industries. Focused on the efficient transfer of power from source to driven load, this collection examines technological innovations in gears, bearings, chains, drivetrains, and robotic systems. The reprint explores design methodologies that minimize vibrations and optimize performance in power transmission elements. Engineers, researchers, and industry professionals will find valuable insights on crucial issues including friction losses, churning effects, and windage impact that affect transmission efficiency.